2020
DOI: 10.1080/23723556.2020.1822123
|View full text |Cite
|
Sign up to set email alerts
|

Targeting copper metabolism to defeat KRAS-driven colorectal cancer

Abstract: KRAS-driven cancers acquire profound metabolic dependencies that are intimately linked to tumor growth. Our work revealed that colorectal cancers that harbor KRAS mutations are addicted to copper metabolism. This adaptation renders tumor cells critically dependent on the copper transporter ATP7A, which reveals copper metabolism as a promising therapeutic target for KRAS-driven colorectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, it was demonstrated that metabolic adaptions play an important role in highly resistant colorectal cancers with KRAS (Kirsten rat sarcoma 2 viral oncogene homologue) mutation [ 115 ]. Strikingly, these profound metabolic dependencies were also linked to the addiction of KRAS-mutated cancer to Cu metabolism [ 116 , 117 ]. Profiling of KRAS-expressing intestinal epithelioid cells IEC-6 with the combination of state-of-the-art cell surface proteomics and CRISPR/Cas-9 screens identified ATP7A as a lethal synthetic partner in KRAS-mutant colorectal cancers [ 116 ].…”
Section: Tumor Modulation With Inorganic Cu Saltsmentioning
confidence: 99%
“…Recently, it was demonstrated that metabolic adaptions play an important role in highly resistant colorectal cancers with KRAS (Kirsten rat sarcoma 2 viral oncogene homologue) mutation [ 115 ]. Strikingly, these profound metabolic dependencies were also linked to the addiction of KRAS-mutated cancer to Cu metabolism [ 116 , 117 ]. Profiling of KRAS-expressing intestinal epithelioid cells IEC-6 with the combination of state-of-the-art cell surface proteomics and CRISPR/Cas-9 screens identified ATP7A as a lethal synthetic partner in KRAS-mutant colorectal cancers [ 116 ].…”
Section: Tumor Modulation With Inorganic Cu Saltsmentioning
confidence: 99%
“…Accumulated copper ions play a crucial role in CRC progression (Aubert, Nandagopal, Roux, 2020; Aubert, Nandagopal, Steinhart, Lavoie, et al, 2020; Feng et al, 2009; Ishida et al, 2013; Liao et al, 2020; Sen et al, 2001; Shanbhag et al, 2021). To remove intracellular copper ions, copper chelators, such as TM and trientine, have been used to demonstrate the efficacy of this “starvation strategy” (Alvarez et al, 2010; Baldari et al, 2019; Brem et al, 2005; Brewer, 2014; Hyvönen et al, 2016; Jain et al, 2013; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the inflammatory response induces copper uptake through an IL‐17‐STEAP4‐XIAP axis, which promotes tumorigenesis of colorectal cancer (CRC) (Liao et al, 2020). Kirsten rat sarcoma viral oncogene (KRAS) mutated CRC cells acquire copper via a noncanonical mechanism involving macropinocytosis to support their growth, revealing copper metabolism to be a promising therapeutic target for the suppression of KRAS‐driven colorectal cancer (Aubert, Nandagopal, Roux, 2020; Aubert, Nandagopal, Steinhart, Lavoie, et al, 2020). Elevated copper levels were also found to regulate the expression of vascular endothelial growth factor (VEGF) and hypoxia‐inducible factor‐1 (HIF‐1), thus stimulating tumor angiogenesis (Feng et al, 2009; Sen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer and non-small cell lung cancer, the activity and expression of copper-associated transporters are involved in the formation of tumor resistance to cisplatin and other platinum compounds ( 14 ). In COAD, the formation of KRAS-induced tumor and the generation of drug resistance are related to copper metabolism, and the use of copper chelating agent can inhibit the growth of tumor cells ( 17 ). In addition, copper-associated metabolic proteins can enhance the sensitivity of COAD cell lines to oxaliplatin ( 18 ).…”
Section: Discussionmentioning
confidence: 99%